2019
DOI: 10.1523/eneuro.0251-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of Neural Progenitor Cells Impairs Acquisition of Trace Eyeblink Conditioning

Abstract: Adult-born neurons are believed to play a role in memory formation by providing enhanced plasticity to the hippocampus. Past studies have demonstrated that reduction of neurogenesis impairs associative learning, but these experiments used irradiation or neurotoxic substances, which may have had unintended off-target effects. Therefore, to investigate the role of these adult-born neurons more precisely, we used nestin-HSV-TK transgenic mice (Nes-TK) to selectively ablate newborn neurons. Nes-TK mice were fed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Doublecortin is associated with levels of neurogenesis, which has a well-documented role in learning (Miller, Weiss, and Disterhoft 2019;Dalla et al 2009;Deng, Aimone, and Gage 2010). Levels of doublecortin were significantly lower in intact microdrive females and dummy drive females compared to headbolt females.…”
Section: Discussionmentioning
confidence: 97%
“…Doublecortin is associated with levels of neurogenesis, which has a well-documented role in learning (Miller, Weiss, and Disterhoft 2019;Dalla et al 2009;Deng, Aimone, and Gage 2010). Levels of doublecortin were significantly lower in intact microdrive females and dummy drive females compared to headbolt females.…”
Section: Discussionmentioning
confidence: 97%
“…To date, sex differences in function have gone largely undetected because few studies have compared male and female animals that have altered neurogenesis. In our recent analysis of the literature ( Knudson et al, 2022 ), we counted only four functional studies that have reported data by sex or included sex as a variable in their statistical analyses ( Huckleberry et al, 2018 ; Seib et al, 2018 ; Miller et al, 2019 ; Cope et al, 2020 ). Very recently, two studies have identified functional differences in male and female rodents that lack adult neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…5A). Layering information was extracted from the CSD data based on the well corroborated fact that the CSD signal at a fixed latency of 5-10 ms after a pulse-like whisker deflection is known to show two sinks, one centered on L4, the other on the border of L5 and L6 (=L5/6) 25,26 . We did not find any depth profile of the specific ranking of stimulus types.…”
Section: Resultsmentioning
confidence: 99%